2009
DOI: 10.1186/1471-2121-10-90
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular diffusion restrictions in isolated cardiomyocytes from rainbow trout

Abstract: BackgroundRestriction of intracellular diffusion of adenine nucleotides has been studied intensively on adult rat cardiomyocytes. However, their cause and role in vivo is still uncertain. Intracellular membrane structures have been suggested to play a role. We therefore chose to study cardiomyocytes from rainbow trout (Oncorhynchus mykiss), which are thinner and have fewer intracellular membrane structures than adult rat cardiomyocytes. Previous studies suggest that trout permeabilized cardiac fibers also have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…In rat heart, the apparent magnitude of diffusion restrictions increases during ontogeny ( 3 ) and is diminished by ischemia-reperfusion damage of the tissue ( 4 ). Similar diffusion restrictions have been identified in cardiomyocytes of ectothermic vertebrates ( 5 ) and have been found to depend on acclimation conditions in turtles ( 6 ). In comparison, cultured cardiomyocytes, which do not contract against a workload and depend more on glycolytic than aerobic metabolism, have almost no diffusion restrictions ( 7 ).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In rat heart, the apparent magnitude of diffusion restrictions increases during ontogeny ( 3 ) and is diminished by ischemia-reperfusion damage of the tissue ( 4 ). Similar diffusion restrictions have been identified in cardiomyocytes of ectothermic vertebrates ( 5 ) and have been found to depend on acclimation conditions in turtles ( 6 ). In comparison, cultured cardiomyocytes, which do not contract against a workload and depend more on glycolytic than aerobic metabolism, have almost no diffusion restrictions ( 7 ).…”
Section: Introductionsupporting
confidence: 76%
“…However, fiber preparations can be heterogeneous in terms of diffusion distance, as compared to a suspension of permeabilized cardiomyocytes. As a result, the use of cardiomyocytes to study intracellular energy transfer has increased recently ( 5,17,18 ). However, a systematic study of intracellular diffusion patterns is needed for input into mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…However, variable thermal sensitivities between permeabilized preparations and isolated mitochondria from the same species have been described before. Permeabilized rainbow trout cardiac fibres and isolated cardiomyocytes were virtually insensitive to temperature, while isolated mitochondria exhibited significant reductions in respiration rates with decreasing temperature (Sokolova et al, 2009). The authors of the study could not give an explanation for the variable effects of temperature in the different preparations.…”
Section: Temperature Sensitivity Of Respiration Through Etc Complexesmentioning
confidence: 93%
“…These restrictions have been attributed to low permeability of the outer mitochondrial membrane and cytosolic diffusion restrictions (Andrienko et al, 2003;Saks et al, 1995). Additionally, the different K m ADP of permeabilized preparations may simply be a result of insufficient cell separation or clustering of fibres in the respirometer (Sokolova et al, 2009). Ectothermic cardiomyocytes have a relatively simple morphology with low volumes and high surface-area to volume ratios (Galli et al, 2006), but intracellular diffusion restrictions have also been reported in the rainbow trout.…”
Section: Apparent K M Of Adp Affinitymentioning
confidence: 96%
See 1 more Smart Citation